2015
DOI: 10.26708/ijmsc.2015.1.5.10
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Approach for Solving Fuzzy Matrix Games

Abstract: In this paper, two-person matrix games is considered whose elements of pay-off matrix are triangular fuzzy numbers (TFNs). To solve such game a new method based on α-cut of TFN is developed for each of the players. In this method, two auxiliary bi-objective linear programming (BOLP) models are derived. Then using average weighted approach these two BOLP models are decomposed into two auxiliary crisp linear programming (LP) problems. Finally, the value of the matrix game for each player is obtained by solving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Li 17 proposed a lexicographic method to study fuzzy matrix games. Seikh et al 18 implemented an α-cut based approach to study matrix games with fuzzy pay-offs. Jana and Roy 19 analyzed the solution approach of matrix games with generalized trapezoidal fuzzy payoffs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li 17 proposed a lexicographic method to study fuzzy matrix games. Seikh et al 18 implemented an α-cut based approach to study matrix games with fuzzy pay-offs. Jana and Roy 19 analyzed the solution approach of matrix games with generalized trapezoidal fuzzy payoffs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…http://www.ijmp.jor.br v. 12, n. 1, January-February 2021 ISSN: 2236-269X DOI: 10.14807/ijmp.v12i1.1295 Recently, a zero-sum matrix game model with Dmpster-Shafer belief structure payoffs was developed, and a decomposition method was proposed to calculate the value of such a game which is expressed with belief structures (Deng, Jiang & Zhang, 2017). An alternating method was developed to solve the matrix games (Seikh, Nayak & Pal, 2013). The fuzzy matrix games are with very high degree of inconsistent information and indetermination.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…Recently, Shiekh et al [34] proposed the solution of matrix games with rough interval pay-offs and its application in the telecom market share problem. Shiekh et al [35] suggested an alternative approach for solving fuzzy matrix games. Ruidas et al [36] developed a productionrepairing inventory model considering demand and the proportion of defective items as rough intervals.…”
Section: Introductionmentioning
confidence: 99%